1999
DOI: 10.1038/sj.hdy.6884400
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic pleiotropy and genetic polymorphism: a perspective

Abstract: Antagonistic pleiotropy, in which reproduction and viability counter each other, appears to be widely thought of great significance in life history theory and the evolution of senescence. However, the conditions for maintenance of polymorphism by antagonistic pleiotropy are quite restrictive. This is particularly so when there is no reversal of dominance for different traits, sex-limited expression of fitness components, finite population size or inbreeding. Furthermore, when antagonistic pleiotropy is compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
104
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 30 publications
4
104
1
Order By: Relevance
“…AP could have caused some of the increase in the additive component. Also, AP can lead to senescence even if pleiotropic genes contribute very little genetic variation, because selection can cause near fixation of alleles with beneficial early and deleterious late effects and near elimination of alleles with the reverse pattern of action (41,42). Indeed, many of the recently discovered ''aging'' genes in Drosophila and other model organisms may fall into this category (43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…AP could have caused some of the increase in the additive component. Also, AP can lead to senescence even if pleiotropic genes contribute very little genetic variation, because selection can cause near fixation of alleles with beneficial early and deleterious late effects and near elimination of alleles with the reverse pattern of action (41,42). Indeed, many of the recently discovered ''aging'' genes in Drosophila and other model organisms may fall into this category (43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…The idea that polymorphism may be maintained by antagonistic pleiotropy (when mutations with deleterious effects on some characters have beneficial effects on other characters) (Rose, 1982) is popular and appealing, even though, initially Rose (1982) and more recently Curtsinger et al (1994) and Hedrick (1999) have shown that conditions for polymorphism at pleiotropic loci with antagonistic effects on fitness are rather restrictive. Therefore, even if trade-offs in fitness components have been reported to occur in nature (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Trait-specific dominance has been studied previously in models for the maintenance of genetic variation by pleiotropic antagonistic effects of an allele on two fitness components (Rose 1982;Curtsinger et al 1994;Hedrick 1999). These models, with additive effects of fitness components, can be easily generalized to an arbitrary number of fitness components or phenotypic traits and to arbitrary patterns of pleiotropic effects.…”
Section: Antagonistic Pleiotropy and Trait-specific Dominancementioning
confidence: 99%
“…Models that have considered trait-specific dominance and dominance reversals focus on antagonistic pleiotropy between two fitness components (Rose 1982;Curtsinger et al 1994;Hedrick 1999). Although these models were constructed to investigate the contribution of pleiotropy to the maintenance of genetic variation, they showed that trait-specific dominance facilitates the maintenance of genetic variation by antagonistic pleiotropy.…”
mentioning
confidence: 99%
See 1 more Smart Citation